1992
DOI: 10.1055/s-2007-999260
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Atypical Cervical Cytology in Pregnancy

Abstract: To ascertain the significance of squamous atypia encountered during routine Papanicolaou smear screening in pregnancy, we reviewed our experience with 76 pregnant women seen during a 4-year period. All were evaluated with repeat cytology and colposcopy during pregnancy and again postpartum. Colposcopic examination during pregnancy revealed a normal transformation zone without evidence of intraepithelial neoplasia in 46 women. In six of these women, repeat cytology was interpreted as cervical intraepithelial ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
6

Year Published

1995
1995
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 12 publications
1
36
0
6
Order By: Relevance
“…18,19 Current evidence points to HPV subtypes as the most important single factor in the etiology of cervical neoplasia 9,14,[20][21][22][23] but one report underplays its role. 11 A previous study in Jordanian females suggested little role of sexually transmitted disease in pelvic inflammatory disease 24 but this does not exclude HPV in the etiology of CIN. Table 1 demonstrates a similar pattern of CIN grades in the two groups but in group 2, lower CIN grades were more frequent, suggesting better awareness in this latter group.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…18,19 Current evidence points to HPV subtypes as the most important single factor in the etiology of cervical neoplasia 9,14,[20][21][22][23] but one report underplays its role. 11 A previous study in Jordanian females suggested little role of sexually transmitted disease in pelvic inflammatory disease 24 but this does not exclude HPV in the etiology of CIN. Table 1 demonstrates a similar pattern of CIN grades in the two groups but in group 2, lower CIN grades were more frequent, suggesting better awareness in this latter group.…”
Section: Discussionmentioning
confidence: 97%
“…Absence of CIN in our females who were above 60 is in accordance with other reports in which CIN de novo was either infrequent or absent in females over 50 years of age. 11,12 Frequency of CIN in screened groups within selected patient populations were relatively high; for example, 8% in one California study on emergency ward patients 13 while in another from Seattle, development of CIN at two years was seen in 3% and 28% of HPV negative and positive females respectively. 14 Table 2 shows a stepwise increase of incidence rates in females between the ages of 20 and 49 years with a fall during the sixth decade.…”
Section: Discussionmentioning
confidence: 99%
“…21% in pre-gnant women is 260. 4 Pregnant women who never have pap smear in last three years were included and following women were excluded. Pregnant women who have negative pap smear in last three years, patients with threatened miscarriage and patients with low lying placenta.…”
Section: Methodsmentioning
confidence: 99%
“…76 cases of pregnant patients that showed 21% CIN in pap smear samples. 4 Similarly, studies conducted in Pakistan and India screened both obstetrics and gynaecological patients showed up to 5% of cervical epithetlial abnormalities. 5,6 It means that study conducted in antenatal population showed high incidence of CIN as compared to both obstetrics and gynae patients.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation